A Single-Institution Cohort Study With Nevi of Special Site: Recurrence, Progression to Melanoma, and Patterns of Management. (2nd January 2023) - Elkeeb, Dena M.; Hopkins, Zachary H.; Bolender, Caitlin M.; Moreno, Christopher; Florell, Scott R.; Bowen, Anneli R.; Vitale, Patricia; Zussman, Jamie; Duffy, Keith; Grossman, Douglas; Secrest, Aaron M.; Wada, David A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Nevi of specialized sites (NOSS) occur on the scalp, ears, flexural, acral, and genital areas and display atypical clinical and histologic features. We assessed NOSS recurrence and progression to melanoma, management patterns, and associations between histologic features and treatment recommendations. We queried all histologic diagnoses of NOSS (n = 275) from 2012 to 2017 from a large U.S. academic medical center with reference dermatopathology laboratory and matched these to clinical records. A blinded panel of dermatopathologists re-evaluated lesions, catalogued histologic findings, and gave management recommendation. Associations with dermatopathologist decision and concordance between new and original recommendations were assessed. Of 117 cases with follow-up, 2 locally recurred (1.46%) and none eventuated in melanoma. Clinical features were not associated with original treatment recommendations. After histopathologic review, large melanocytes [odds ratio ratio (ORR) = 8.00, 95% CI, 1.35–47.4] and junctional mitotic figures (ORR = 65.0, 6.5–650) predicted excision recommendation. Likewise, accumulation of many (>9) high-risk features was associated with excision recommendation. Panel review changed treatment recommendation in 27% of cases. Fair concordance existed between original and panel recommendations (κ = 0.29, 0.15–0.44). The low rate of recurrence and lack of melanoma occurrence suggest that despite an atypical clinical and histopathologic appearance, these nevi have limited potential for malignant transformation. Histopathologic findings seem to be principal drivers behind the recommendation for excision in this analysis. Variability existed in treatment recommendations; the panel's consensus recommendation tended to downgrade treatment. This highlights the importance of further outcomes-based studies to identify true high-risk features and refine management guidelines.